1997
DOI: 10.1074/jbc.272.1.13
|View full text |Cite
|
Sign up to set email alerts
|

Geranylgeranylated Rho Small GTPase(s) Are Essential for the Degradation of p27 and Facilitate the Progression from G1 to S Phase in Growth-stimulated Rat FRTL-5 Cells

Abstract: Cyclin-dependent kinase (Cdk) enzymes are activated for entry into the S phase of the cell cycle. Elimination of Cdk inhibitor protein p27 Kip1 during the G 1 to S phase is required for the activation process. An inhibitor of 3-hydroxy-3-methylglutaryl-CoA reductase prevents its elimination and leads to G 1 arrest. Mevalonate and its metabolite, geranylgeranyl pyrophosphate, but not farnesyl pyrophosphate, restore the inhibitory effect of pravastatin on the degradation of p27 and allow Cdk2 activation. By the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
162
1
1

Year Published

1998
1998
2007
2007

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 221 publications
(173 citation statements)
references
References 30 publications
9
162
1
1
Order By: Relevance
“…If the cytoskeleton is disassembled prior to a cell reaching the restriction point, growth is arrested (Zhu et al, 1996). Other reports have indicated that RhoA stimulates cell cycle progression through inactivation of the cyclin dependent kinase inhibitors (CKIs) p27 Kip1 (Hirai et al, 1997) or p21 Cip1 (Olson et al, 1998). Our results suggest that, activation of RhoA results in actin stress ®ber assembly, which would provide the signals leading to cell proliferation.…”
Section: Discussionmentioning
confidence: 55%
See 2 more Smart Citations
“…If the cytoskeleton is disassembled prior to a cell reaching the restriction point, growth is arrested (Zhu et al, 1996). Other reports have indicated that RhoA stimulates cell cycle progression through inactivation of the cyclin dependent kinase inhibitors (CKIs) p27 Kip1 (Hirai et al, 1997) or p21 Cip1 (Olson et al, 1998). Our results suggest that, activation of RhoA results in actin stress ®ber assembly, which would provide the signals leading to cell proliferation.…”
Section: Discussionmentioning
confidence: 55%
“…Our results suggest that, activation of RhoA results in actin stress ®ber assembly, which would provide the signals leading to cell proliferation. These signals may be mediated by the CKIs p27 Kip1 and p21 Cip1 (Hirai et al, 1997;Olson et al, 1998). Under conditions where RhoA might be expected to be active (e.g.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the results obtained with lovastatin, an inhibitor of HMG-CoA (3-hydroxy-3-methylglutaryl coenzyme A) reductase which blocks the posttranslational modi®cation (isoprenylation) of small GTP binding proteins such as Rho and Ras, indicate that small GTP binding proteins are not involved in p21 degradation. In contrast, both Rho and Ras have been suggested to play an important role in the degradation of the related CKI p27 (Hirai et al, 1997;Kawada et al, 1997).…”
Section: Resultsmentioning
confidence: 99%
“…It appears that the signals from Ga 12/13 are translated into growth-promoting signals by the small GTPases Ras, Rac, and Rho. It has been reported that Ras, Rho, Rac, and CDC42 play an essential role in cell cycle progression from G1 to S phase (Aktas et al, 1997;Takuwa and Takuwa, 1997;Olson et al, 1995;Hirai et al, 1997). An additional role for Rac in progression from G2 to M phase has been also identi®ed (Moore et al, 1997).…”
Section: Ga 12/13 : the Gep Oncogenes?mentioning
confidence: 99%